Fertilidade do solo e características produtivas de propriedades familiares de produção de leite do sudoeste paranaense - Franceschi, Fernando (2018)
The objective of this study was to diagnose the chemical status of the soil and the production system of dairy farms in Southwest Paraná. The identification/characterization of the properties (n = 36) occurred from technical visits, in which a technical, productive and socio-cultural questionnaire was carried out. Information was also collected regarding the size of the property, type, cultivation system and history of cultivation and soil management. Soil samples were collected from areas with pastures (perennial and annual), annual crops (corn and soybean) and areas for the fallow of animals, totaling 102 areas. The samples were identified, packed and sent to the Soil Laboratory of UTFPR. In the areas grazed by lactating cows, the number of animals was quantified. The forage mass of these areas was estimated visually. The animal load (kg/ha) and the stocking rate (UA/ha) were estimated from the mean body weight of lactating dairy cows. The milk production of the areas was estimated from the number of lactating animals and the volume produced during the month of the visit. Non-parametric statistics were used to analyze the data. Cultures destined to the fallow of animals showed a higher content of organic matter (OM) in relation to the annual and perennial crops, in which 100 % of the areas destined to the fallow of animals presented MO of the "very high" soil. Annual and perennial crops presented 87.2 % and 80.8 % of their areas with "very high" OM content, respectively. It was verified that 56.2 % of the areas destined to the fallow of animals presented P content classified as "very high", whereas only 26.7 % of the areas with annual crops and 27.0 % of the areas with perennial pastures presented content of soil P classified as "very high". Likewise, it was verified that the percentage of areas destined to the fallow of animals with "very high" K content was 50.0 %, higher than the percentage of areas with annual crops (21.7 % of the areas) and perennial crops (19.3 % of the areas) with said classification for the content of this element. The sum of the "high" and "very high" pH classes accounted for 46.7 %, 48.4 % and 62.6 % of the areas with annual, perennial and fallow crops, respectively. The stocking rate (animals/ha) and milk production (kg/ha) were higher (P < 0.05) in perennial pastures compared to annual summer pastures. No difference (P > 0.05) was found for milk protein and fat content between perennial and annual summer pastures. Only 39 % of the properties met the minimum requirements for somatic cell count and total bacterial count.